Key facts series: Key facts sheet on inequality - Hami, Emmanuel (International Food Policy Research Institute, 2022)
Across a wide range of inequality measures, survey data measure lower levels of inequality in 2019/20 compared to a decade earlier in 2010/11. The latest survey data put Malawi’s Gini Coefficient at 0.38. The 20% richest households consume about half of the country’s total consumption. The poorest 20% account for only 6% of total consumption. Differences between districts or regions are not the primary contributors to inequality. Differences across households within the same region or district contribute much more to total inequality. Similarly, there is significant inequality among households with heads of similar education levels and among those with similar occupations. These within-group differences contribute more to inequality than the across-group differences. In all the periods under analysis, urban households consumed around twice the consumption of their rural counterparts.